Research and Implementation of Network Public Opinion Rrediction System. (June 2020) - Chen, Xuegang; Gao, Shouping; Duan, Sheng; Wang, Luda
Abstract: The Internet has become a distribution center of ideological and cultural information and an amplifier of public opinion. To dig, analyze and study hot public opinions on the Internet is an important means to fully understand what netizens are thinking and doing. This paper analyzes the function of public opinion system, and introduces the key technology to realize the prediction of network public opinion, which can well realize the prediction function of public opinion.